2023
DOI: 10.3390/molecules28062547
|View full text |Cite
|
Sign up to set email alerts
|

Nitrile Oxide, Alkenes, Dipolar Cycloaddition, Isomerization and Metathesis Involved in the Syntheses of 2-Isoxazolines

Abstract: The involvement of 1,3-dipolar cycloaddition (1,3-DP), double bond migration, metathesis, and nitrile oxide (including in situ-generated nitrile oxide) as dipoles, together with the C=C bond containing dipolarophiles, in the syntheses of 2-isoxazolines is presented. Methods for synthesizing isoxazolines (other than 1,3-DP cycloaddition) were also presented briefly. Various methods of nitrile oxide preparation, especially in situ-generated procedures, are presented. Special attention was paid to the application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 356 publications
(757 reference statements)
0
7
0
Order By: Relevance
“…Substituent in position 4 of the benzene ring of the reagents 2 did not affect the ratio of regioisomers: for NOs 2a, 2b, 2c, 2f fundamentally different in electronic nature (Table 1, entries [1][2][3]6), almost the same ratio of isomers was obtained. On the contrary, the steric factor had a more noticeable effect on this ratio: for NOs having substituents in positions 2,6 of the benzene ring 2d and 2e (entries 4, 5), the amount of isomers 5 was significantly higher.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Substituent in position 4 of the benzene ring of the reagents 2 did not affect the ratio of regioisomers: for NOs 2a, 2b, 2c, 2f fundamentally different in electronic nature (Table 1, entries [1][2][3]6), almost the same ratio of isomers was obtained. On the contrary, the steric factor had a more noticeable effect on this ratio: for NOs having substituents in positions 2,6 of the benzene ring 2d and 2e (entries 4, 5), the amount of isomers 5 was significantly higher.…”
Section: Resultsmentioning
confidence: 89%
“…IR spectra were registered on a Varian 3100 FTIR spectrometer in 4000-400 cm À1 range. 1 H and 13 C spectra were run in CDCl 3 at room temperature on Bruker DPX-400 spectrometer (400.13, 100.61 MHz, respectively). Chemical shifts were referred to residual signals of CDCl 3 (7.27 for 1 H, 77.160 for 13 C).…”
Section: General Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common and efficient approaches found in the literature for synthesis of isoxazole derivatives involve [3 + 2] dipolar cycloaddition between nitrile oxides and alkynes or alkenes, [159] and condensation of hydroxylamine with 1,3dicarbonyl compounds or its equivalents. [160] Sloop et al reported that the reaction of 1 with hydroxylamine 55 in presence of sulfuric acid leads to mixture of 3(5)trifluoromethylisoxazoles 235 and 236 (R=Me) or a single product, 3-trifluoromethylisoxazole 235 (R=Ph) (Scheme 74).…”
Section: Isoxazole Derivativesmentioning
confidence: 99%
“…The most common and efficient approaches found in the literature for synthesis of isoxazole derivatives involve [3+2] dipolar cycloaddition between nitrile oxides and alkynes or alkenes, [159] and condensation of hydroxylamine with 1,3‐dicarbonyl compounds or its equivalents [160] …”
Section: Trifluoromethyl‐β‐dicarbonyls Based Synthesis Of Heterocyclesmentioning
confidence: 99%